p66Shc Links α(1)-Adrenergic Receptors to a Reactive Oxygen Species–Dependent AKT-FOXO3A Phosphorylation Pathway in Cardiomyocytes - Guo, Jianfen (2009)
p66Shc is an adapter protein that is induced by hypertrophic stimuli and has been implicated as a major regulator of reactive oxygen species (ROS) production and cardiovascular oxidative stress responses. This study implicates p66Shc in an α(1)-adrenergtic receptor (α(1)-AR) pathway that requires the cooperative effects of protein kinase (PK)Cε and PKCδ and leads to AKT-FOXO3a phosphorylation in cardiomyocytes. α(1)-ARs promote p66Shc-YY(239/240) phosphorylation via a ROS-dependent mechanism that is localized to caveolae and requires epidermal growth factor receptor (EGFR) and PKCε activity. α(1)-ARs also increase p66Shc-S(36) phosphorylation via an EGFR transactivation pathway involving PKCδ. p66Shc links α(1)-ARs to an AKT signaling pathway that selectively phosphorylates/inactivates FOXO transcription factors and downregulates the ROS-scavenging protein manganese superoxide dismutase (MnSOD); the α(1)-AR-p66Shc-dependent pathway involving AKT does not regulate GSK3. Additional studies show that RNA interference–mediated downregulation of endogenous p66Shc leads to the derepression of FOXO3a-regulated genes such as MnSOD, p27Kip1, and BIM-1. p66Shc downregulation also increases proliferating cell nuclear antigen expression and induces cardiomyocyte hypertrophy, suggesting that p66Shc exerts an antihypertrophic action in neonatal cardiomyocytes. The novel α(1)-AR– and ROS-dependent pathway involving p66Shc identified in this study is likely to contribute to cardiomyocyte remodeling and the evolution of heart failure.